Tinjauan Yuridis Tentang Surat Perintah Penghentian Penyidikan (SP3) Terhadap Kasus Penipuan - Gani Hadi Surya Sembiring; Ridho Mubarak; Alvin Hamzah Nasution (Universitas Medan Area, 2021)
Law Number 8 of 1981 concerning Criminal Procedure Law authorizes investigators to terminate investigations. The purpose of writing this thesis is to find out the legal considerations of the North Sumatra Regional Police in issuing an Investigation Cessation Warrant in fraud cases and legal remedies for the issuance of an Investigation Cessation Order in fraud cases. The type of research used in this research is normative juridical and the research method used in this thesis is library research and field research at the North Sumatra Regional Police by taking data and interviews with staff at Poda North Sumatra, which are related to with a warrant for termination of investigation and regarding cases of fraud according to the title of the investigator. The conclusion drawn in this thesis is that in issuing a warrant for termination of investigation in a fraud case, the legal considerations of the North Sumatra Regional Police are insufficient evidence, the incident is not a criminal act, and is terminated by law. Legal Remedies Against the Order to Stop Investigation (SP3) in the Fraud Case are ordinary legal remedies and extraordinary legal remedies.